The Development of Religious Concepts among Muslim Student in Yogyakarta - Maizida, Karlina (DINIKA : Academic Journal of Islamic Studies, 2017)
This study aims to examine the religious development of Muslim children through their opinions about religion as well as their experience. It is intended to explore their understanding of some religious concepts and the factors influencing their understanding. The main participants of this study are six children in one of the religious private modernist schools in Yogyakarta from the first until the sixth grades (their ages are around 7-12 year old). The researcher expects that the children religious concept develops in accordance with the cognitive development theory. Moreover, since all participants are Muslim, it is expected that there is a different nuance from the previous research which particularly discusses the concept of God. If social environment takes an account of children religious concept, the researcher expects to find out which aspect is more dominant: the aspect of family or the aspect of the school. The results showed that the children religious concept grows as something inseparable from the rest of the children development, from concrete to more abstract knowledge, from simple to more complicated view. The social environment, particularly religious instruction at school, plays a central role in the children's religious concept.